2014
DOI: 10.1007/s40279-014-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Matrix Metalloproteinase-9 and -2 to Exercise

Abstract: Alterations in MMP-9 and MMP-2 plasma concentrations may be valuable biomarkers to reflect the influence of exercise on the inflammatory state. Nevertheless, the limited evidence available regarding the effects of exercise on the MMP-9 and MMP-2 response in human participants suggests that further studies are needed to fully define the connection between the role of exercise on the MMP-9 and MMP-2 response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 49 publications
1
24
0
2
Order By: Relevance
“…Motility of cancer cells is associated with its invasiveness through extracellular matrix. Metastasis of human HCC cells may request both high motility of HCC cell as well as the ability of tumor cell in degenerating extracellular matrix [ 34 , 35 , 36 ]. To further investigate the possible anti-metastasis effect of berberine in HCC cells, we conducted a transwell chamber assay to observe the effect of berberine on invasiveness of tumor cell through extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motility of cancer cells is associated with its invasiveness through extracellular matrix. Metastasis of human HCC cells may request both high motility of HCC cell as well as the ability of tumor cell in degenerating extracellular matrix [ 34 , 35 , 36 ]. To further investigate the possible anti-metastasis effect of berberine in HCC cells, we conducted a transwell chamber assay to observe the effect of berberine on invasiveness of tumor cell through extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the initiating and essential step of tumor cell invasion is to break through from the restriction of extracellular matrix by degrading local proteins. The most important executors for proteolysis are MMPs [ 34 , 35 , 36 ]. Furthermore, such process is controlled by some signaling pathways including PAI-1, tPA, uPA and TIMPs [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One more probable mechanism is the decrement of TNF-α induced by the training, a well-known exciter of MMP-9 production. Results revealed that chronic aerobic training leads to cardio protective effects and is useful for the prevention of diabetes, hypertension, cancer, osteoporosis, and dementia (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous human studies have demonstrated that physical exercise can affect the levels of MMPs following acute and chronic interventions. Under coronary risk events, the elevations of MMP-2 and MMP-9 are correlated with increased inflammation [ 21 ]. The decrease in MMPs could be related to expression of the tissue inhibitors of metalloproteinases (TIMPs), protease degradation, and reduction of proinflammatory cytokine tumor necrosis factor-alpha (TNF- α ) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%